Effect of Implantation of Cryopreserved Placental Explants on Behaviour Structure in Female Mice of Late Ontogenesis - Chub, Oleg V.; Musatova, Irina B.; Prokopyuk, Vladimir Yu.; Karpenko, Vladimir G. (Problems of Cryobiology and Cryomedicine, 2015)
N/A